MONITORING OF QUALITY OF LIFE IN PATIENTS WITH ARTERIAL HYPERTENSION OF OLDER AGE GROUPS - Khaydarova Zarrina Erkinovna; Yarmukhamedova Saodat Khabibovna; Vafoeva Nigora Abrorovna (Academia Science Repository, 2023)
Arterial hypertension (AH), as in all countries with developed economies, is one of the urgent medical and social problems. It is one of the most common diseases in old age. About 50% of people aged 60-69 years and more than 75% in the age group over 70 years have elevated blood pressure (BP). It is shown that with each decade of life, the prevalence of arterial hypertension increases by about 10%, reaching a maximum (75%) in people over 70 years of age. Consequently, the risk of vascular events increases significantly with age, primarily cerebral stroke and myocardial infarction, which annually claim the lives of about 12 million people in the world. Therefore, the quality of hypertension treatment largely determines the quality and life expectancy of the population.